Recent trends in atmospheric methyl bromide: analysis of post-Montreal Protocol variability - S. A. Yvon-Lewis; E. S. Saltzman; S. A. Montzka (Atmospheric Chemistry and Physics, 2009)
The atmospheric methyl bromide (CH3Br) burden has declined in recent years, in response to the phaseout of agricultural and structural fumigation consumption under the amendments to the Montreal Protocol. The timing and magnitude of this decrease represents an opportunity to examine our current understanding of atmospheric CH3Br and its budget, response to the phaseout, and response to interannual variability in biomass burning and global OH. In this study, simulations obtained from a time-dependent global model of atmospheric CH3Br emissions and uptake are compared to observations from the NOAA flask network. The model includes a detailed gridded ocean model coupled to a time-dependant atmospheric 2-box model. The phaseout of CH3Br production for agricultural uses began in 1998, concurrent with the pulse in biomass burning associated with the 1998 El Niño. The combined effects of three factors (biomass burning, global OH, and anthropogenic phaseout) appear to explain most of the observed atmospheric methyl bromide variability over the 1997–2008 period. The global budget remains imbalanced, with a large missing source indicated. The missing source does not exhibit a systematic decline during the phaseout period, and therefore, is not the result of significantly underestimating non-QPS agricultural CH3Br emissions. The model results suggest that the oceans should be less undersaturated than before the phaseout began.